Temperature Dependence of Testes Intersticium Cell Membrane Permeability for Cryoprotectant Molecules - Chernobai, N. A.; Pakhomov, A. V.; Kovalenko, I. F.; Bozhok, G. A.; Kovalenko, S. Ye.; Rozanov, L. F. (Problems of Cryobiology and Cryomedicine, 2010)
Osmotic behavior of the rat testis intersticium cells in cryoprotectants solutions – substances belonging to alcohols (ethylene glycol (EG), glycerol and 1,2-butane diol (1,2-BD)), oxides (dimethyl sulfoxide (Me2SO)) and amides (dimethyl formamide (DMFA)) was studied. Permeability coefficients of testis cells for these cryoprotectants were determined at 35, 20 and 5°C by volumetric analysis and the Kedem-Kachalsky modified physico-mathematical model. The calculated values of the activation energies for EG, glycerol, 1,2-BD, Me2SO and DMFA molecules are 53.28, 46.92, 36.33, 58.89, 62.99 kJ/mol, respectively. Testis cell membranes were established to be equally well permeable for EG, glycerol, 1,2-BD and Me2SO, and their permeability for DMFA at 35°C was comparable with that for water molecules.